Phylogenetic Analysis of Nucleus-Encoded Acetyl-CoA Carboxylases Targeted at the Cytosol and Plastid of Algae - Huerlimann, Roger (PLoS One, 2015)
The understanding of algal phylogeny is being impeded by an unknown number of events of horizontal gene transfer (HGT), and primary and secondary/tertiary endosymbiosis. Through these events, previously heterotrophic eukaryotes developed photosynthesis and acquired new biochemical pathways. Acetyl-CoA carboxylase (ACCase) is a key enzyme in the fatty acid synthesis and elongation pathways in algae, where ACCase exists in two locations (cytosol and plastid) and in two forms (homomeric and heteromeric). All algae contain nucleus-encoded homomeric ACCase in the cytosol, independent of the origin of the plastid. Nucleus-encoded homomeric ACCase is also found in plastids of algae that arose from a secondary/tertiary endosymbiotic event. In contrast, plastids of algae that arose from a primary endosymbiotic event contain heteromeric ACCase, which consists of three nucleus-encoded and one plastid-encoded subunits. These properties of ACCase provide the potential to inform on the phylogenetic relationships of hosts and their plastids, allowing different hypothesis of endosymbiotic events to be tested. Alveolata (Dinoflagellata and Apicomplexa) and Chromista (Stramenopiles, Haptophyta and Cryptophyta) have traditionally been grouped together as Chromalveolata, forming the red lineage. However, recent genetic evidence groups the Stramenopiles, Alveolata and green plastid containing Rhizaria as SAR, excluding Haptophyta and Cryptophyta. Sequences coding for plastid and cytosol targeted homomeric ACCases were isolated from Isochrysis aff. galbana (TISO), Chromera velia and Nannochloropsis oculata, representing three taxonomic groups for which sequences were lacking. Phylogenetic analyses show that cytosolic ACCase strongly supports the SAR grouping. Conversely, plastidial ACCase groups the SAR with the Haptophyta, Cryptophyta and Prasinophyceae (Chlorophyta). These two ACCase based, phylogenetic relationships suggest that the plastidial homomeric ACCase was acquired by the Haptophyta, Cryptophyta and SAR, before the photosynthetic Rhizaria acquired their green plastid. Additionally, plastidial ACCase was derived by HGT from an ancestor or relative of the Prasinophyceae and not by duplication of cytosolic ACCase.